2023
DOI: 10.3390/en16237753
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Generation Trend and Bioenergy Recovery Potential: A Review

James Darmey,
Julius Cudjoe Ahiekpor,
Satyanarayana Narra
et al.

Abstract: Finding sustainable solutions to the increasing waste generation in Ghana has received a lot of attention in recent years. Through several waste-to-energy processes, the energy potential of municipal solid waste has recently witnessed significant technological advancements. The Renewable Energy Master Plan has projected the production of about 122 MWp from waste-to-energy installations by 2030 in Ghana. To help policymakers and engineers achieve national goals, this paper reviews the waste generation in Ghana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Additionally, gasification efficiency is heavily contingent on the physical and chemical quality and composition of the feedstock. Ghana's municipal solid waste (MSW) exhibits heterogeneity, including high moisture content and contamination, necessitating complex and costly pre-treatment processes such as drying, sorting, and size reduction [75]. While gasification offers cleaner emissions compared to conventional incineration, air pollution risks persist.…”
Section: Gasificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, gasification efficiency is heavily contingent on the physical and chemical quality and composition of the feedstock. Ghana's municipal solid waste (MSW) exhibits heterogeneity, including high moisture content and contamination, necessitating complex and costly pre-treatment processes such as drying, sorting, and size reduction [75]. While gasification offers cleaner emissions compared to conventional incineration, air pollution risks persist.…”
Section: Gasificationmentioning
confidence: 99%
“…This scarcity not only poses safety risks but also has the potential to contribute to greenhouse gas emissions. Consequently, there is a pressing need for the implementation of robust leak detection and mitigation strategies, as emphasized by [75].…”
Section: Landfill Gas (Lfg)mentioning
confidence: 99%
“…Many previous studies have proven the energy recovery potential of waste in Ghana [45][46][47]. For instance, it has been estimated that 13,000 GWh of energy can be recovered from waste by 2030 [48]. However, the government has failed to prioritize achieving this goal.…”
Section: Justification For and Objective Of This Studymentioning
confidence: 99%
“…This can gradually be implemented by identifying the hotspots in the country for waste generation, which is also linked to the population. Various studies have identified metropolitan areas as the most important hotspots for waste generation, with a high potential for renewable energy through waste [46,48,55]. More importantly, urban areas have a higher waste generation rate due to their consumption patterns, and the collection rate was reported as 51.4% for urban areas, as compared to 5.8% for rural areas [88].…”
Section: Quantity Of Waste Generated and Treatedmentioning
confidence: 99%
“…Therefore, it would be worthwhile to produce valuable chemicals and products from an MSW-handling industry. In the upcoming years, with the growing population of Ontario, it will be crucial to address the proper conversion of these waste materials into useful chemicals and products [27]. The economic feasibility of biobased materials relies on the optimization of their efficiency and the reduction in toxic gas emissions during pyrolysis, gasification, and combustion processes.…”
Section: Introductionmentioning
confidence: 99%